Detection of deviance in Japanese kanji compound words - Egashira, Yuka; Kaga, Yoshimi; Gunji, Atsuko; Kita, Yosuke; Kimura, Motohiro; Hironaga, Naruhito; Takeichi, Hiroshige; Hayashi, Sayuri; Kaneko, Yuu; Takahashi, Hidetoshi; Hanakawa, Takashi; Okada, Takashi; et al. (Frontiers in Human Neuroscience, 2022)
Reading fluency is based on the automatic visual recognition of words. As a manifestation of the automatic processing of words, an automatic deviance detection of visual word stimuli can be observed in the early stages of visual recognition. To clarify whether this phenomenon occurs with Japanese kanji compounds—since their lexicality is related to semantic association—we investigated the brain response by utilising three types of deviants: differences in font type, lexically correct or incorrect Japanese kanji compound words and pseudo-kanji characters modified from correct and incorrect compounds. We employed magnetoencephalography (MEG) to evaluate the spatiotemporal profiles of the related brain regions. The study included 22 adult native Japanese speakers (16 females). The abovementioned three kinds of stimuli containing 20% deviants were presented during the MEG measurement. Activity in the occipital pole region of the brain was observed upon the detection of font-type deviance within 250 ms of stimulus onset. Although no significant activity upon detecting lexically correct/incorrect kanji compounds or pseudo-kanji character deviations was observed, the activity in the posterior transverse region of the collateral sulcus—which is a fusiform neighbouring area—was larger when detecting lexically correct kanji compounds than when detecting pseudo-kanji characters. Taken together, these results support the notion that the automatic detection of deviance in kanji compounds may be limited to a low-level feature, such as the stimulus stroke thickness.